Diseño del sistema de gestión de seguridad y salud en el trabajo para la empresa constructora obras y bustillo s.a.s. De la ciudad de candelaria (2016)
The construction company WORKS AND BUSTILLO S.A.S., is an entity that has several offices, its headquarters is in MONTELIBANO CORDOBA which is dedicated to the construction of civil works. It consists of a headquarters in Candelaria Valle (INGENIO MAYAGUEZ) dedicated to transporting materials such as ash filter cake, stillage sludge and also the unloading coal etc. who is aware of all the aggressive conditions in the labor and environmental from a diagnosis of conditions of safety, health and environment, intends to conduct activities through the subprograms of Preventive Medicine and Labor and Health and Industrial Safety road safety as the work we do, aimed at controlling risk factors, ensuring the health of workers and maintaining quality of life.